The Influence of Socio-cultural Backgrounds on Language Learning - BENDELAL, RAFIK (My University, 2020)
Ethnographic research is used as an observational tool to study and understand social science related topics. In order to investigate culture-related practices, the present research aims to shade light at a set of social experiences that a group of minorities are facing in their educational journey as foreign language learners with different cultural backgrounds. In fact, little attention is given to those of different backgrounds in terms of way of communication or interaction combined with a lack of knowledge of the common cultural attributes and concepts. To underline those experiences and to highlight the importance of culture-related concepts, important culture related concepts are presented in the theoretical part, and as far as the practical part of this research is concerned ,a set of conversational interviews was conducted with twenty students belonging to various cultural minority backgrounds to demonstrate and show what they have been experiencing as minorities and to underline the main obstacles found in cross-cultural encounters . The major findings showed that those of different backgrounds are facing unpleasant experiences and are exposed to misunderstanding when socializing . In the light of those results , different suggestions and recommendations are presented to raise awareness regarding overcoming such incidences.
Case of study: Minorities in Abdel Hamid Ibn Badis University of Mostaganem
Keywords: Culture; Minorities; Cross-cultural encounter; Communication; Interaction